Mechanical Strength of Additive Manufactured Carbon Fiber Reinforced Polyetheretherketone; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Chumaevskii A. V.; Tarasov S. Yu. Sergei Yulievich; Filippov A. V. Andrey Vladimirovich; Kolubaev Е. А. Evgeny Aleksandrovich; Rubtsov V. E. Valery Evgenjevich; Eliseev A. A. (2016, 2016)
Title screen